Bridging or Limiting Inclusion? Deaf Perspectives on Sign Language Interpretation in Zambian Education - Kenneth Kapalu Muzata; Rachel Muuma Chomba (Universal Education, 2025)
This study explores the attitudes of persons with deafness toward sign language interpretation as a means of inclusion in Zambia’s educational system. Although sign language interpretation is widely considered a critical tool for bridging communication barriers, its effectiveness depends on how it is perceived and experienced by those it seeks to serve. Guided by a qualitative research design, semi-structured interviews were conducted with deaf learners to capture their perspectives on the benefits, limitations, and challenges of interpretation services. The findings reveal a duality of attitudes: while interpretation fosters access to information, confidence, and participation in mainstream education, it also raises concerns about dependency, misrepresentation, and the erosion of opportunities for direct communication between deaf and hearing individuals. Attitudes varied by gender and onset of deafness, with postlingual participants emphasizing interpreter competence and prelingual participants advocating for teachers to acquire direct sign language skills. The study concludes that sign language interpretation is valuable but insufficient on its own for genuine inclusion. It recommends investment in both professional interpreter training and sign language proficiency among educators to strengthen sustainable, inclusive education in Zambia.